ПРАГМА-СЕМАНТИЧНІ ПІДТИПИ ВОЛІТИВНИХ ВИСЛОВЛЕНЬ В КОНСТИТУЦІЙНОМУ ДИСКУРСІ НІМЕЧЧИНИ - Сушко-Безденежних, Марія Григорівна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article deals with the illocutionary aspect of the discourse of Gennan constitutions at clause (minimal utterance) level. These utterances belong to deontic modality area bearing the common meaning of volition - direct imperative causing of certain states of affairs in the society or actions of social actors. 20 semanticpragmatic subtypes of imperative utterances are singled out on the basis of positive nonn structure in Deontic Logic. Those subtypes are classified into the illocutionary classes directive, declarative and commissive.